ANALYSIS OF THE FOOD ACQUISITION PROGRAM IN PINHALZINHO - COUNTY - SC AS REPRODUCTION STRATEGY OF SOCIO-ECONOMIC FAMILY PRODUCTION - Hentz, Carla [UNESP] (Univ Federal Roraima, 2016)
This article focuses on the rural development of public policies for family farming, more specifically the Food Acquisition Program (PAA). The aim is to analyze the marketing possibilities offered by the establishment of this public policy, and to what extent, this has fostered economic and social alternatives for small family farmers are able to insert autonomously on the market, overcoming the hegemonic model based on the system integration with the processing agribusinesses operating in the state of Santa Catarina. To achieve this goal, considering how the study area the municipality of Pinhalzinho - SC, we worked with data from secondary and primary sources. In addition, it performed extensive bibliography about the themes: public policies for rural development and family farming. The results show that PAA is constituted as an important public policy, especially as an accessory alternative source of income for the household. On the other hand, research has highlighted gaps that limit a break with the dominant production model in western Santa Catarina region.
Keywords: Public policies for rural development; Family farming; Food Acquisition Program - PAA; Pinhalzinho - SC